UPAYA MEDIASI DALAM MEMINIMALISIR ANGKA PERCERAIAN DI PENGADILAN AGAMA KELAS I B WATAMPONE - Syafruddin Syafruddin (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2020)
AbstractThis research aims to describe the mediation efforts in minimizing the number of divorces in the Religious Courts 1B Watampone, the opportunities, constraints, faced and the efforts to minimize the number of divorces in the Religious Class 1B Watampone. This research was classified as qualitative research by using the descriptive-normative approach to theological normative, juridical-normative, psychological, and sociological The results showed that the mediation efforts in minimizing the number of divorces in the Religious Court 1B Watampone carried out in two phases: the implementation of the results of mediation and the implementation phase of mediation. The absence of pre-mediation on mediation with in the Religious Courts Watampone Class 1B because the process converges on the implementation phase of the mediation itself.